Effects of ECM proteins (laminin, fibronectin, and type IV collagen) on the biological behavior of Schwann cells and their roles in the process of remyelination after peripheral nerve injury - Yu, Peng; Zhang, Guanhua; Hou, Bo; Song, Enpeng; Wen, Jiaming; Ba, Yueyang; Zhu, Donglin; Wang, Gangwei; Qin, Feng (Frontiers in Bioengineering and Biotechnology, 2023)
After peripheral nerve injury (PNI), remyelination is a critical step for functional nerve regeneration, and regenerated axons can only play a part after complete myelination and the formation of myelinated fibers. Suboptimal myelin regeneration is a common phenomenon, making it difficult to achieve ideal nerve regeneration. The relationship between the extracellular matrix (ECM) and Schwann cells (SCs) in the nerve regeneration environment is extremely close. This study tries to analyze and compare the effects of three kinds of ECM proteins on the biological behaviors of SCs (adhesion, proliferation, and migration) as well as the use of engineered neural scaffolds based on composite sodium alginate hydrogel with ECM components and explores the effects of ECM proteins on remyelination after PNI. The results showed that laminin (LN), fibronectin (FN), and collagen Ⅳ (type IV Col) promoted the early adhesion of SCs in 2-dimensional culture but the ratios of early cell adhesion were quite different and the maintenance of cells’ morphology by different ECM proteins were significantly different. In transwell experiment, the ability of LN and FN to induce the migration of SCs was obviously higher than that of type IV Col. An vitro co-culture model of SCs and dorsal root ganglia (DRG) neurons showed that LN promoted the transition of SCs to a myelinated state and the maturation of the myelin sheath, and increased the thickness of neurofilaments. The number of SCs arranging along neurofilaments was significantly higher in the LN group. Interestingly, FN can promote the maturation of SCs but cannot induce remyelination, and type IV Col can promote neither the maturation of SCs nor myelin regeneration. The animal experiment indicated that the effects of LN in promoting myelin sheath formation, axon repair and reaching an ideal G-ratio after injury were generally better than that of FN and of type IV Col. The situation of gastrocnemius atrophy was significantly better in the LN group. The LN group had more myelin sheaths alongside the regenerated nerve filaments. Notably, the thickness of the regenerated myelin sheaths in the type IV Col group was the thickest.